Effectiveness of Civil Servants’ Performance Through Budget Participation and Organizational Citizenship Behavior (OCB): A Literature Review - Sabdan, Sitti Rahmatiah; Nitri Mirosea; Husin, Husin (Dinasti Publisher, 2025)
The effectiveness of civil servants' performance (ASN) is a key factor in achieving accountable public governance. This study aims to examine the relationship between budget participation and Organizational Citizenship Behavior (OCB) in enhancing ASN performance effectiveness through a literature review approach. The findings indicate that ASN participation in the budgeting process strengthens their understanding of organizational goals and fosters a greater sense of responsibility in program implementation. Meanwhile, OCB—which includes voluntary behaviors such as assisting colleagues and demonstrating concern for the organization— contributes to the creation of a collaborative and productive work culture. The integration of budget participation and OCB generates a positive synergy that enhances ASN performance effectiveness. This study highlights the importance of bureaucratic reform that promotes active participation and proactive work behavior within the framework of accountability and transparency in public financial management.